Non-metal doping induced dual p-n charge properties in a single ZnIn₂ S₄ crystal structure provoking charge transfer behaviors and boosting photocatalytic hydrogen generation - Chong, Wei-Kean (2023)
Construction of heterojunction is conventionally regarded as the prevailing technique to render effective solar-driven photocatalytic water splitting. Nonetheless, realization of p-n homojunction emerges to be an appealing scheme attributed to the non-defective layer coupling and minor charge transfer impedance. Herein, nitrogen-doped ZnIn2S4 (N-ZIS) with dual p-n charge properties was facilely synthesized via one-step in-situ solvothermal method. Systematic investigations unveil that the substituting phenomenon of hosting S by extrinsic N atom with dissimilar electronegativity and valence electron, which eventually ameliorates charge transfer rate and inhibits electron-hole pairs recombination. First-principle density functional theory calculations affirm the p-nature induced by N-doping imparting favorable charge redistribution in the ZIS framework and diminishing hydrogen (H2) evolution reaction kinetic barrier at the surface-active sites. Therein, optimal N-ZIS generated 1575.71 μmol∙g−1 of H2 under 6-hour visible-light irradiation (with an apparent quantum yield of 6.59 % at 420 nm monochromatic light irradiation), which is 6.35-fold than the pristine counterpart.